2022
DOI: 10.1144/petgeo2021-074
|View full text |Cite
|
Sign up to set email alerts
|

Negatively buoyant CO 2 solution sequestration in synformal traps

Abstract: Dissolving CO2 into water or brine produces a denser fluid than the CO2-free equivalent at all salinity, temperature and pressure conditions relevant to sedimentary basins. Negative buoyancy of CO2 solutions opens the possibility of utilizing negative relief trapping configurations for CO2 sequestration, as opposed to structural highs conventionally sought for positively buoyant fluids such as hydrocarbons or pure CO2. Exploring sedimentary basins for negative buoyancy traps can readily utilize hydrocarbon exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 96 publications
1
0
0
Order By: Relevance
“…Finally, supercritical CO 2 (scCO 2) ) is a relatively dense fluid phase (with a liquid-like density) although the viscosity is gas-like under the existing reservoir pressure and temperature conditions that exceed the respective critical points. In most sedimentary basins, the pressure and temperature requirements for scCO 2 are reached at depths greater than approximately 750-900 m (Stewart, 2022;Stewart and Riddell, 2022). In the current study, a reservoir burial depth of 800 m is assumed; this agrees with Chadwick et al (2009) who also suggested depths greater than 800 m at pressures >8 MPa for optimizing the storage efficiency.…”
Section: Masupporting
confidence: 80%
“…Finally, supercritical CO 2 (scCO 2) ) is a relatively dense fluid phase (with a liquid-like density) although the viscosity is gas-like under the existing reservoir pressure and temperature conditions that exceed the respective critical points. In most sedimentary basins, the pressure and temperature requirements for scCO 2 are reached at depths greater than approximately 750-900 m (Stewart, 2022;Stewart and Riddell, 2022). In the current study, a reservoir burial depth of 800 m is assumed; this agrees with Chadwick et al (2009) who also suggested depths greater than 800 m at pressures >8 MPa for optimizing the storage efficiency.…”
Section: Masupporting
confidence: 80%